2019
DOI: 10.1111/cyt.12712
|View full text |Cite
|
Sign up to set email alerts
|

The role of rapid on‐site evaluation on diagnostic accuracy of endoscopic ultrasound fine needle aspiration for pancreatic, submucosal upper gastrointestinal tract and adjacent lesions

Abstract: Background and Aim Our aim was to assess adequacy and diagnostic accuracy of endoscopic ultrasound‐fine needle aspiration (EUS‐FNA) specimens with or without rapid on‐site evaluation (ROSE) from pancreatic, upper gastrointestinal tract (UGIT) and adjacent masses. Method A retrospective cohort study based on patients’ files who underwent EUS‐FNA in Galilee Medical Center in a 4 years period. Number of needle passes, repeated EUS and ROSE effect on tissue adequacy and diagnostic accuracy were reported. Results O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The results showed that leiomyomas in the esophagus were significantly more than cysts, and leiomyomas in the upper esophagus were significantly less than those in the middle and lower esophagus, and the difference was statistically significant ( P < 0.05). There were more stromal tumors in the bottom and body of the stomach than in other parts, and the ectopic pancreas in the antrum was significantly more than that in other parts, and the difference was statistically significant ( P < 0.05), which was consistent with the result of Khoury et al [ 28 ]. At last, the study compared the diagnostic effects of ultrasound combined with gastroscope on upper gastrointestinal submucous occasions.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that leiomyomas in the esophagus were significantly more than cysts, and leiomyomas in the upper esophagus were significantly less than those in the middle and lower esophagus, and the difference was statistically significant ( P < 0.05). There were more stromal tumors in the bottom and body of the stomach than in other parts, and the ectopic pancreas in the antrum was significantly more than that in other parts, and the difference was statistically significant ( P < 0.05), which was consistent with the result of Khoury et al [ 28 ]. At last, the study compared the diagnostic effects of ultrasound combined with gastroscope on upper gastrointestinal submucous occasions.…”
Section: Discussionsupporting
confidence: 90%
“…Guidelines released by the European Society of Gastrointestinal Endoscopy (ESGE) recommend a minimum of 20 to 30 supervised EUS-FNAs in the presence of rapid onsite cytopathological examination (ROSE) to reach sufficient competency in this technique and sensitivity for pathological diagnosis up to 80% [21]. The importance of ROSE in increasing EUS-FNA diagnostic accuracy and reducing the number of passes needed to obtain sufficient tissue specimens is largely debated [22]. However, the presence of a cytopathologist in the endoscopy room may be limited for a number of practical reasons, such as local availability and high costs.…”
Section: Introductionmentioning
confidence: 99%
“…Massive studies have already been published regarding the diagnostic yield of EUS-FNAB. 22 - 56 A meta-analysis published in 2016 reports that EUS-guided sampling of upper gastrointestinal subepithelial lesions is safe, but has a moderate diagnostic ability (59.9%) regardless of techniques of FNA/FNB/Tru-Cut needle biopsy or the needle diameter used for puncture. 57 Conversely, a successive meta-analysis reveals that sampling ability of FNA (80.6%) is significantly lower to that of FNB (94.9%), but increase with the help of rapid on-site evaluation.…”
Section: Eus-guided Fine-needle Aspiration/biopsymentioning
confidence: 99%